2018
DOI: 10.1186/s40104-018-0273-x
|View full text |Cite
|
Sign up to set email alerts
|

Alginate oligosaccharide-induced intestinal morphology, barrier function and epithelium apoptosis modifications have beneficial effects on the growth performance of weaned pigs

Abstract: BackgroundAlginate oligosaccharide (AOS), produced from alginate by alginate lyase-mediated depolymerisation, is a potential substitute for antibiotics and possesses growth-enhancing effects. Nevertheless, the mechanisms by which AOS regulates porcine growth remain to be elucidated. Therefore, we investigated the AOS-mediated changes in the growth performance of weaned pigs by determining the intestinal morphology, barrier function, as well as epithelium apoptosis.MethodsTwenty-four weaned pigs were distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 56 publications
(50 reference statements)
1
32
0
Order By: Relevance
“…Mice were maintained under a light: dark cycle of 12:12 h and at a temperature of 23 o C and humidity of 50-70%; they had free access to food (chow diet) and water. 36 In our preliminary study (based on early report: Wan et al 22 ), AOS 10 mg/kg body weight dosing for two weeks was the best treatment condition for improving busulfan disrupted small intestine (1, 5, 10, 20 mg/kg body weight of AOS dosing for 1, 2, 3, and 4 weeks). Three-week-old ICR male mice were given a single injection of 40 mg/kg body weight (BW) of busulfan.…”
Section: Materials and Methods [Detailed Methods In Supplemental Infomentioning
confidence: 81%
See 1 more Smart Citation
“…Mice were maintained under a light: dark cycle of 12:12 h and at a temperature of 23 o C and humidity of 50-70%; they had free access to food (chow diet) and water. 36 In our preliminary study (based on early report: Wan et al 22 ), AOS 10 mg/kg body weight dosing for two weeks was the best treatment condition for improving busulfan disrupted small intestine (1, 5, 10, 20 mg/kg body weight of AOS dosing for 1, 2, 3, and 4 weeks). Three-week-old ICR male mice were given a single injection of 40 mg/kg body weight (BW) of busulfan.…”
Section: Materials and Methods [Detailed Methods In Supplemental Infomentioning
confidence: 81%
“…21 AOS benefits intestinal morphology and barrier function by increasing the length of intestinal villi, the content of secretory immunoglobulin A, and the number of Goblet cells. 22 However, the underlying mechanisms of how AOS improve small intestine morphology and function from the single intestinal cell level is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Reverse transcription was performed using a Prime Script RT Reagent Kit with gDNA Eraser (Takara, Dalian, China). The mRNA levels of the selected genes in the colon were determined by real-time quantitative (RT-qPCR) as described previously (Li et al, 2015; Wan et al, 2017, Wan et al, 2018b). Selected genes were corresponding to the following proteins: epithelial cell proteins, including E -cadherin, occludin, and zonula occludens-1 (ZO-1); anti-inflammatory cytokines, including interleukin-4 (IL-4), IL-10 and transforming growth factor-beta-1 (TGF-β1); proinflammatory cytokines, including granulocyte-macrophage colony-stimulating factor (GM-CSF), IL-1α, IL-1β, IL-2, IL-12, and tumor necrosis factor alpha (TNF-α); toll-like receptor 4 (TLR4) signaling pathway proteins, including cluster of differentiation 14 (CD14) and TLR4.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, higher ZO-1 protein expression in the jejunum at weaning was noticed after maternal Tau supplementation, suggesting that maternal dietary supplementation with Tau could enhance the intestinal physical barrier function of offspring. Tau supplementation increased jejunum sIgA content at weaning, suggesting that maternal dietary supplementation with Tau could enhance the intestinal immune barrier function of offspring [40,41]. These results revealed that Tau contributes to repair the oxidative stress-associated intestinal barrier dysfunction in piglets and possibly to improve their growth performance.…”
Section: Discussionmentioning
confidence: 99%